Optimizing Different Gypseous Soil Characteristics Incorporating Clayey Soil - Wattar, Zainulabdeen Hussein Al; Al-Kifae, Abdulaziz A. (Al-Nahrain Journal for Engineering Sciences, 2025)
Gypsum soil is classified as problematic because it contains gypsum, a soluble substance in the presence of water. Therefore, it is recommended that it be improved before construction. This research examines the effect of clayey soils on enhancing the properties of gypseous soils. Two soil samples, designated as Soil 1 (with a gypsum concentration of 35.4%) and Soil 2 (with a gypsum content of 12.3%), were obtained from Al Najaf City, Iraq, and subjected to laboratory testing. The study investigates the use of cost-effective, locally available clayey soil to improve the engineering characteristics of gypseous soils, thereby mitigating the adverse effects of wetting. The experimental program encompassed a compaction, compressibility, and shear strength test. To assess the impact of clayey additives, gypseous soil was treated with varying percentages of clayey soil content (5% and 10%), and tests were conducted on both treated and untreated gypseous soil samples. The results indicated that using 10% clayey additives could decrease the collapse potential by 55% and 39% for Soil 1 and Soil 2, respectively. Additionally, the clayey additives significantly affected cohesion, with an enhancement percentage of 625% and 1315% under soaking conditions at 10% clayey additives for Soil 1 and Soil 2, respectively.